The Thermochemistry of Alkyne Insertion into a Palladacycle Outlines the Solvation Conundrum in DFT. Issue 45 (17th November 2021) - Milovanović, Milan R.; Boucher, Mélanie; Cornaton, Yann; Zarić, Snežana D.; Pfeffer, Michel; Djukic, Jean‐Pierre
Abstract: In an effort to determine the thermochemistry of established organometallic transformation, the well documented reaction of alkynes with a palladacycle was investigated by isothermal titration calorimetry (ITC). Although the mechanism of the insertion of unsaturated substrates into the Pd−C bond of cyclopalladated compounds is known, no information is available so far about their thermochemistry. The enthalpies of the reactions of Ph−C≡C−Ph and MeOC(O)−C≡C(O)COMe with the bisacetonitrilo salt of the N, N ‐benzylamine palladacycle were determined by ITC in chlorobenzene after having optimized the conditions to ensure that only the double and a single insertion of alkynes were occurring respectively. The reaction energy profile established by DFT for the double insertion process involving Ph−C≡C−Ph confirmed earlier conclusions on the rate determining character of the first insertion. Further computations of reaction enthalpies reveal significant discrepancies between ITC and DFT‐D/continuum solvation enthalpies, that are suspected to arise from an unexpected explicit noncovalent interaction of PhCl with the components of the reaction. Abstract : Enthalpies of reactions of alkynes with a palladacycle determined by isotherm titration calorimetry in chlorobenzene reveal major solvation‐related discrepancies with a standard continuum solvation‐DFT approach.